2009
DOI: 10.1016/j.jana.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Stages of Change, Decisional Balance, and Self-Efficacy in Condom Use Among Rural African-American Stimulant Users

Abstract: This pilot study (a) examined the stages of change (SOC) for condom use with primary and casual partners among rural heterosexual African American stimulant users, (b) identified gender differences in variables associated with SOC, and (c) assessed the association of SOC with decisional balance and self-efficacy. Seventy-two participants completed the study. SOC with a primary partner was much lower than SOC with a casual partner, indicating more consistent condom use with casual partners. Significant gender d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 39 publications
(73 reference statements)
4
19
0
9
Order By: Relevance
“…In a sample of HIV positive injection drug users (IDU) 26 , men were more likely than women to endorse the beliefs that, with condoms, sex doesn’t feel as good or as natural. Among rural heterosexual African American stimulant users 27 , women reported more advantages to condom use on a decisional balance measure. These studies reinforce that differences exist between men and women when it comes to condom beliefs and sexual risk behavior.…”
Section: Introductionmentioning
confidence: 95%
“…In a sample of HIV positive injection drug users (IDU) 26 , men were more likely than women to endorse the beliefs that, with condoms, sex doesn’t feel as good or as natural. Among rural heterosexual African American stimulant users 27 , women reported more advantages to condom use on a decisional balance measure. These studies reinforce that differences exist between men and women when it comes to condom beliefs and sexual risk behavior.…”
Section: Introductionmentioning
confidence: 95%
“…21-23 A study that examined condom use by casual and primary relationship status found that African-American men were less likely to use condoms with primary partners. 24 The current study findings that a) reported consistent condom use was significantly greater among those reporting current monogamy and b) odds of consistent condom use increased in proportion to the number of recent female sex partners reported, may indicate a positive response to the AIDS epidemic in rural Florida from African-American men. Despite engaging in concurrent partnerships, these men may indeed be aware of HIV risk.…”
mentioning
confidence: 55%
“…ATS use can increase individuals' sexual desire and pleasure responses, weaken their self-control, and result in failure to use condoms. Self-efficacy and gender empowerment have been reported to be important factors that determine condom use among drug users (Gullette et al, 2009; Tony et al, 2010). The findings of this study provide clinical evidence that prevention and treatment need to target these behaviors and problems.…”
Section: Discussionmentioning
confidence: 99%